ANALISIS MODEL KONSEPTUAL DEBIT AIR PADA DAS INDRAGIRI HILIR MENGGUNAKAN MODEL IHACRES - Jusatria Jusatria (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2020)
The modelling of Indragiri Hilir drainage basin is very necessary, considered by Indragiri Hilir area which sometimes overflows into residential areas and disturbs residents' activities. Conceptual analysis of water discharge through the Ihacres software could help to analyze the flow of Indragiri Hilir drainage basin. Rainfall-runoff modeling is used to predict runoff values, one of which is the IHACRES model. The IHACRES model produces nonlinear loss module parameters and linear hydrograph module units. AWLR that will be used is Kuantan Rengat station, Rain Data that will be used are from Tembilahan station and climatology from Air Molek station. Determination of the success of the model used equation R2 and R to calculate the deviation that occurs. The calibration, verification and simulation phase starts in 2010-2015. The result of conceptual analysis of water discharge of Indragiri Hilir drainage basin, In the calibration stage of the IHACRES Model, the best scheme is scheme 2 with R2 value 0.861 and R value 0.864. While the verification phase is carried out with the following year the best scheme is scheme 3 with the highest R2 value with R2 -2,550 and R-value 1,603 and the simulation scheme is the best scheme 5 with R2-1,904 and R-1,341.